The perspective of the chinese linguaculture on the characteristics of the beginning and the end of russian official letters - - Wu Sujuan (Russian Language Studies, 2009)
The article is devoted to the perspective of the Chinese linguaculture on the characteristics of the beginning and the end of Russian official letters.